Remixing war: An analysis of the reimagination of the Russian–Ukraine war on TikTok - Primig, Florian; Szabó, Hanna Dorottya; Lacasa, Pilar (Frontiers in Political Science, 2023)
Interpretative struggles of global crises are increasingly being reflected on social media networks. TikTok is a relatively new social media platform that has achieved substantial popularity among young people in many parts of the world and is now being used to disseminate and make sense of information about the Russian invasion of Ukraine. Through a user-centered sampling approach, we collected 62 TikTok videos and conducted an in-depth qualitative analysis of them and their uploading profiles to explore how the war was being represented on the platform. Our analysis revealed a strong prevalence of remixing practices among content creators; that is, they recontextualise images, sounds and embodied self-performance within the platform-specific affordances of trends. We found that distant suffering is mediated through the emotive online self-performance of content creators, cuing their audiences toward appropriate emotional responses. Trending sounds situate videos within a singular-motif and context-diverse environment, facilitating what we theorize as affective audio networks.